Estudo da variação do teor de umidade e sólidos totais voláteis dos resíduos sólidos urbanos, com a precipitação pluviométrica e suas implicações na geração de lixiviados no aterro sanitário integrado de Cruz das Almas – BA - Oliveira, Agda da Luz (2011)
This work presents the results of physical (gravimetric composition and water content) and physic-chemical characterization (volatile total solids and lignin content) of the municipal solid wastes (MSW) disposed in the Cruz das Almas landfill, as to identify the variation of water content and volatile total solids to the local rainfall. This research was developed by sampling domestic solid wastes during the year of 2010, in eight different months. The samples were collected from the wastes when they arrived at the landfill (fresh wastes) and before they were disposed in cell 1. The data of rainfall were collected at EMBRAPA climatological station and pluviometer in the landfill. The water contents of the studied wastes were plotted versus rainfall registred at the city as the generated leachat versus rainfall registred at the landfill. The results of gravimetric composition have shown that the wastes have the major amount of paste component, followed by plastics and carbon paper in wet and dry basis. The values of calculated water content varied between 37% and 56% (wet basis), 59% and 127% (dry basis). The volatile total solids obtained values were between 33% and 64%, and they indicate the presence of a high organic matter content in the wastes, in agreement to their age (young waste). It was observed a low linear co-relation between volatile total solids and the initial water content of the studied wastes to both applied methodologies: Carvalho (R2 = 0,40) and CETESB (R2 = 0,16). The samples with high wet content presented the highest volatile total solids values. The lignin content obtained values were between 23% and 44,3% and they were higher than presented values at national and international literature. The initial water content of the wastes that come to the landfill tend to increase with the rainfall at the city. But it`s necessary to evaluate a long period, more than 01 (one) year. The leachate generated into the cell 1 and the rainfall in the landfill have similar behavior. It was verified that the municipal solid wastes have an amount of liquid around 37,43% - 55,83% of the total weight of the wastes and that liquid stays into the cell.